Antithrombotic Therapies: Near‐Infrared Light Activated Thermosensitive Ion Channel to Remotely Control Transgene System for Thrombolysis Therapy (Small 27/2019). Issue 27 (5th July 2019) - Zhang, Da; Zhang, Cuilin; Lan, Shanyou; Huang, Yanbing; Liu, Jingfeng; Li, Juan; Liu, Xiaolong; Yang, Huanghao
Abstract : In article number 1901176, Juan Li, Xiaolong Liu, Huanghao Yang, and co‐workers develop a thrombolysis approach for noninvasive, on‐demand and sustained antithrombotic therapy with bioengineered cells, which could be noninvasively and precisely controlled to produce urokinase plasminogen activator (uPA) in situ via an NIR laser to significantly enhance the thrombolysis therapeutic effects by spatiotemporally controlling the local temperature.